A Naganishia in high places: functioning populations or dormant cells from the atmosphere?. Issue 3 (3rd July 2017) - Schmidt, Steven K; Vimercati, Lara; Darcy, John L; Arán, Pablo; Gendron, Eli M.S; Solon, Adam J; Porazinska, Dorota; Dorador, Cristina
ABSTRACT: Here, we review the current state of knowledge concerning high-elevation members of the extremophilic Cryptococcus albidus clade (now classified as the genus Naganishia ). These fungi dominate eukaryotic microbial communities across the highest elevation, soil-like material (tephra) on volcanoes such as Llullaillaco, Socompa, and Saírecabur in the Atacama region of Chile, Argentina, and Bolivia. Recent studies indicate that Naganishia species are among the most resistant organisms to UV radiation, and a strain of N. friedmannii from Volcán Llullaillaco is the first organism that is known to grow during the extreme, diurnal freeze-thaw cycles that occur on a continuous basis at elevations above 6000 m.a.s.l. in the Atacama region. These and other extremophilic traits discussed in this review may serve a dual purpose of allowing Naganishia species to survive long-distance transport through the atmosphere and to survive the extreme conditions found at high elevations. Current evidence indicates that there are frequent dispersal events between high-elevation volcanoes of Atacama region and the Dry Valleys of Antarctica via "Rossby Wave" merging of the polar and sub-tropical jet streams. This dispersal hypothesis needs further verification, as does the hypothesis that Naganishia species are flexible "opportunitrophs" that can grow during rare periods of water (from melting snow) and nutrient availability (from Aeolian inputs) in one of the most extreme terrestrial habitats on Earth.